3D printed biodegradable hydrogel-based multichannel nerve conduits mimicking peripheral nerve fascicules - Woo-Youl Maeng; Yerim Lee; Szu-Han Chen; Kyung Su Kim; Daeun Sung; Wan-Ling Tseng; Gyu-Nam Kim; Young-Hag Koh; Yuan-Yu Hsueh; Jahyun Koo (Materials Today Bio)
Treating peripheral nerve injury (PNI) is a prevalent clinical challenge. The improper dispersion of regenerating axons makes it difficult to develop nerve guidance conduits (NGCs) for treating PNI. The multichannel NGCs, designed to mimic the fascicular structure of nerves, are proposed as an alternative to single hollow lumen NGCs. Hydrogel-based NGCs with microscale multichannels resembling actual nerve fascicles are fabricated using digital light processing as 3D printing. Gelatin methacryloyl (GelMA) and polyethylene glycol diacrylate (PEGDA), which are biodegradable and photocurable, are used as the printing solution. The addition of a food-grade dye to the printing solution can prevent overcuring by adjusting the optical path length of light and regulating the polymerization rate. This work further demonstrates that the addition of dyes can enable high-resolution printing, resulting in the achievement of fine multichannels with a diameter of 200 μm. In vivo animal studies using a rat sciatic nerve gap model show that GelMA/PEGDA-based multichannel NGCs can significantly improve peripheral nerve regeneration, as indicated by improved paw sensory recoveries, increased hindlimb gait function, and muscle fiber regeneration. Furthermore, the mechanical properties, pore size, and biodegradation rate of the hydrogel constituting the NGCs successfully demonstrate the feasibility of hydrogel-based multichannel NGCs for accelerating neurologic recoveries.